PENGEMBANGAN MULTIMEDIA PEMBELAJARAN SD PADA MATERI PENGGOLONGAN HEWAN BERDASARKAN JENIS MAKANANNYA TEMA 5 (EKOSISTEM) KELAS V SD - Miranti, Anggun; Nuriya, Asri; Harjanto, Ambyah (Pedagogia: Jurnal Ilmiah Pendidikan Dasar Indonesia, 2019)
This study aims to develop a multimedia product as a learning medium for elementary schools. The research method used is research and development method. The resulting product is in the form of an animation learning video in class V theme 5, a subject of Natural Science with the material of Animal Classification by Type of Food. The conclusion is that the use of multimedia is important because it can arouse students interest in learning, help students understand the material, help teachers to deliver material, train teachers to innovate and take advantage of existing technology, and become a fun learning medium.